Network Security Implementation Against Sniffing Attacks in the IT Services Department of PT Pupuk Sriwidjaja (PUSRI) Palembang - Ardiansyah (Jurnal Jaringan Komputer dan Keamanan, 2025)
Network security is a crucial aspect of maintaining data integrity, confidentiality, and availability within organizations. Sniffing attacks, in which an attacker intercepts and monitors data transmitted over a network, pose a significant threat to data protection. This study aims to analyze the performance of the network security system of the IT Services Department at PT Pupuk Sriwidjaja (PUSRI) Palembang against sniffing threats. The research includes evaluating existing security systems, testing potential sniffing attacks, and implementing and analyzing the effectiveness of various security mechanisms such as encryption, network segmentation, and intrusion detection. The results indicate that appropriate security mechanisms substantially reduce the risk of sniffing attacks. This study also provides recommendations for further improvements, including staff training on cybersecurity best practices and strengthening real-time network monitoring.